Barton Warren Stone Early American Advocate of Christian Unity - West, William Garrett (Disciples of Christ Historical Society, 1954)
Based on the Reed Lectures from 1967, Smith traces the anti-clerical message that accompanied the frontier religious preaching of Alexander Campbell and Barton Stone. Their hopes were that congregations could appoint their own leaders without the undue influence of outsiders. These evangelists were to be first and foremost servants, with no distinction between lay members and ministers. Smith, then traces the development of a professional ministry system within Disciples of Christ into the 1960s as churches called for greater levels of training among their preachers. Chapters include: ▪ A Nineteenth Century Revolution: A Free Ministry in a Free Society ▪ Pastors-Evangelists-Bishops and Sometimes Deacons ▪ Changing Ministries for Changing Times